Analisis Teknologi Charger Untuk Kendaraan Listrik - Review - Kamajaya, Firdaus Sutra; Ulya, Muhammad Muzmi (Jurnal Rekayasa Mesin, 2015)
Electric vehicles are a choice for the future. Therefore, the electric vehicle will be spreads in the community. The public is the average consumer who does not have knowledge about electric vehicles, especially for problem charger. Charger technology in an Electric Vehicle Supply Equipment (EVSE) consists of three types, namely AC level 1, AC level 2 and DC fast charging. Each type has advantages and disadvantages. The disadvantage of AC level 1 type is take a long time for charging (about 20 hours) and the advantage is no risk of damaging the battery. AC level 2 has shortcomings that are still relatively long time to process the charge but shorter process than the AC charge level 1 and there is no high risk of damaging to the battery. DC fast charging has excesscharge process is very short (express)at range 20-30 minutes, but the disatvantage is very high risk of damaging the batteries in continuous usage.This paper also provide discussion for placement of any type of charger, so that people will understand.